Synthesis and Antimicrobial Activity of the Hybrid Molecules between Sulfonamides and Active Antimicrobial Pleuromutilin Derivative. (18th December 2014) - Chen, Liangzhu; Yang, Dexue; Pan, Zhikun; Lai, Lihong; Liu, Jianhua; Fang, Binghu; Shi, Shuning
<x xml:space="preserve">Abstract</x> A series of novel hybrid molecules between sulfonamides and active antimicrobial 14‐o‐(3‐carboxy‐phenylsulfide)‐mutilin were synthesized, and their in vitro antibacterial activities were evaluated by the broth microdilution. Results indicated that these compounds displayed potent antimicrobial activities in vitro against various drug‐susceptible and drug‐resistant Gram‐positive bacteria such as Staphylococci and streptococci, including methicillin‐resistant Staphylococcus aureus, and mycoplasma. In particular, sulfapyridine analog (6c) exhibited more potent inhibitory activity against Gram‐positive bacteria and mycoplasma, including Staphylococcus aureus (MIC = 0.016–0.063 μg/mL), methicillin‐resistant Staphylococcus aureus (MIC = 0.016 μg/mL), Streptococcus pneumoniae (MIC = 0.032–0.063 μg/mL), Mycoplasma gallisepticum (MIC = 0.004 μg/mL), with respect to other synthesized compounds and reference drugs sulfonamide (MIC = 8–128 μg/mL) and valnemulin (MIC = 0.004–0.5 μg/mL). Furthermore, comparison between MIC values of pleuromutilin‐sulfonamide hybrids 6a–f with pleuromutilin parent compound 3 revealed that these modifications at 14 position side chain of the pleuromutilin with benzene sulfonamide could greatly improve the antibacterial activity especially against Gram‐positives.